Impact of globalization and modernization on ethno-confessional and inter-confessional relations in Kazakhstan = Žaһandanu men žaңғyrtudyң Қazaқstandaғy ėtnokonfessijalyқ žәne konfessijaaralyқ қatynastarғa әseri = Vlijanie globalizacii i modernizacii na ėtnokonfessionalʹnye i mežkonfessionalʹnye otnošenija v Kazachstane - Tutinova, Nurgul (Chabaršy. Dintanu serijasy, 2025)
Only in interethnic and interfaith relations can tolerance acquire a concrete content, fulfilling the role of a regulatory mechanism. This article examines the impact of globalization and modernization processes on ethnoconfessional and interfaith relations in Kazakhstan. The aim of the study is to identify the features of the religious situation in the post-Soviet period, the role of a culture of tolerance in a multiethnic society, and its significance for maintaining social stability. The authors analyze the formation and activities of religious organizations, as well as the influence of migration and urbanization on ethnic and interfaith interactions. The research methodology includes content analysis, as well as comparative and historical methods. The scientific novelty of the study lies in the reinterpretation of the concept of tolerance in the context of ethnoconfessional interaction in Kazakhstan. The formation of a culture of tolerance in ethno-confessional relations is one of the current theoretical and practical issues of our multi-ethnic and multi-confessional Kazakhstani society. The main findings include conclusions about the development of interfaith harmony over the past 25 years, the role of religious institutions, and the influence of social processes on ethnoconfessional relations. The significance of the study lies in strengthening the theoretical foundations of interethnic and interfaith dialogue. The practical value of the work is its applicability in domestic policy, public consensus, and intercultural communication.